Integration of Hologram Technology in Entrepreneurship Lockers as Innovative Learning for Students - Gita Claudia; Stephani Inggrit Swastini Dewi; Andre Kurniawan Pamudji; T. Brenda Chandrawati (Journal of Innovation and Community Engagement, 2025)
Entrepreneurship education has become very important in today's digital era, especially in preparing the younger generation to face global economic challenges. Sekolah Nasional Nusaputera has the potential to enhance entrepreneurship literacy through technology, but has experienced a decrease in the use of IoT-based entrepreneurship lockers and cashless payment systems post-Covid-19 pandemic. This research aims to address these issues through the development of hologram technology as a tool to improve students' and teachers' understanding of entrepreneurship and technology literacy. The methods used include needs analysis, the development of interactive hologram content, training, and information dissemination. The results indicate that the use of holograms successfully captured students' interest and improved their understanding of entrepreneurship lockers and digital promotion. However, students also desire further development, including the integration of AI technology and animation, to make learning more interactive. In conclusion, hologram technology has proven effective in enhancing digital promotion and student engagement at Sekolah Nasional Nusaputera, while also opening opportunities for further innovation in this field.